The Effect of the Pre-Screening Questionnaire for Child Development on Increasing Parental Compliance in Monitoring Child Development - Matje Meriaty Huru; Kamilus Mamoh; Diyan Maria Kristin; Agustina Abuk Seran; Mariana Ngundju Awang; Ni Luh Made Diah Putri Anggraeningsih; Maria Florentina Nining Kosad (MEDICA (International Medical Scientific Journal), 2026)
Early childhood represents a critical period for growth and development that substantially influences the quality of future human resources. Therefore, regular developmental monitoring is essential to ensure the early identification of developmental problems. However, parental compliance with child development monitoring remains suboptimal, including in East Penfui Village. The Pre-Screening Developmental Questionnaire (PSDQ/KPSP) is a practical and user-friendly tool that may enhance parental involvement in developmental surveillance. This study aimed to analyze the effect of KPSP utilization on parental compliance in monitoring child development. A pre-experimental study with a one-group pretest–posttest design was conducted among 64 parents of children aged 0–6 years selected through purposive sampling. Data were collected using a respondent characteristics questionnaire, a parental compliance questionnaire, and the KPSP as the intervention instrument. Descriptive statistics were used to summarize respondent characteristics, while the Wilcoxon Signed Rank Test was employed to assess differences in compliance scores before and after the intervention due to the non-normal distribution of data (Shapiro–Wilk test, p < 0.05). The results showed that most respondents were aged 25–35 years, had completed senior high school education, were housewives, and had two to three children. Parental compliance scores increased significantly following the intervention, with the mean score rising from 56.25 ± 10.32 before KPSP implementation to 82.40 ± 8.15 after the intervention. The Wilcoxon Signed Rank Test demonstrated a statistically significant difference between pretest and posttest compliance scores (p < 0.001). The findings indicate that the use of KPSP significantly improves parental compliance in monitoring child development. Integrating KPSP into community-based child health services may strengthen parental participation in developmental surveillance and support the early detection of developmental delays.